Respuesta :

Answer: y=4x^2-40x+107

Just distribute the equation.

y=4(x-5)^2+7

y=4(x^2-10x+25)+7

y=4x^2-40x+100+7

y=4x^2-40x+107

For this case we must change the following equation:

[tex]y = a (x-h) ^ 2 + k[/tex] to the standard form: [tex]y = ax ^ 2 + bx + c[/tex]

By definition we have to:

[tex](a-b) ^ 2 = a ^ 2-2ab + b ^ 2[/tex]

Then, rewriting:

[tex]y = 4 (x-5) ^ 2 + 7\\y = 4 (x ^ 2-2 * 5 * x + 5 ^ 2) +7[/tex]

Applying distributive property to the terms within parentheses:

[tex]y = 4x ^ 2-40x + 100 + 7[/tex]

Finally we have:

[tex]y = 4x ^ 2-40x + 107[/tex]

Answer:

[tex]y = 4x ^ 2-40x + 107[/tex]